PENGARUH MOTIVASI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SRI ONO CATERING - Sri Ermawati; Irwan Raharja (Juremi: Jurnal Riset Ekonomi, 2024)
Abstract This study aims to determine the effect of motivation and work experience on employee performance at PT Sri Ono Catering. This study used quantitative research methods. The sampling method uses the census method with a sample of 35 people. Data collection using the questionnaires methods. The data that was successfully collected was then processed in several stages. First, descriptive analysis. Second, test data quality using validity tests and reliability tests. The three tests of class assumptions consist of normality, multicollinearity test, heteroscedasticity test, and autocorrelation test. Fourth, multiple linear analysis. The five hypothesis tests consist of T test (partial test), F test (simultaneous test). Sixth, test the coefficient of determination. The results showed that partially the motivation variable had a significant effect on employee performance with a calculated value of 3.556 > table 1.692 and a significant value of 0.001 < 0.05. The work experience variable did not have a significant effect on employee performance with a calculated value of 1.218 < table 1.692 and a significant value of 0.232 > 0.05. Silmutantly, the variables of motivation and work experience together have a significant effect on employee performance with a calculated value of 8.602 > table 3.28 and significant 0.001 < 0.05.